(untitled) (Olhar de Professor, 2022)
The interest in researching “educational management and pedagogical practices”, assumes that the role of the manager represents an important educational activity. Thus, the problem is: how do managers think, characterize and enable the conditions for carrying out pedagogical practices in the schools in which they work? With a quanti-qualitative nature, with the subsidy of the Social Representations theory of Moscovici, this research aimed to understand the SR of Basic Education public school managers, about the pedagogical practices carried out by their teachers. 41 managers from 20 municipal and state schools participated. Data were collected through a questionnaire and the free word association technique, treated by the EVOC software. The results show that the SR of the participants about the pedagogical practices developed by their teachers are familiarized with elements that relate to a practice understood as an action that transforms and modifies the school context, but which necessarily needs to be innovative.